Magkapatid - Viva Films (Viva Films, 2002)
Cita (Sharon Cuneta) and Lisa (Judy Ann Santos) are not just sisters but the best of friends. The harmonious relationships is not only between the two siblings but also between their families especially their children. So when a tragedy hits the family, the ideal relationship turns into an ordeal not just for the sisters but for the people around them. Cita was so affected by the incident that she became indifferent, causing even her husband to give up on her. But after sometime, they realize the value of family and try to bring back the harmony in their lives.